Security and effectiveness of arthrocentesis and arthroscopy in the surgical treatment of temporomandibular disorders – literature review - Silva, Lilian Juliana Torres (2024)
Objective: analyze the security and effectiveness of arthrocentesis and arthroscopy techniques in the surgical treatment of temporomandibular disorders. Methodology: this work consists of a narrative literature review of a descriptive nature. Was performed a bibliographical survey through an electronic search in databases: US National Library of Medicine (PubMed), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS) via Biblioteca Virtual em Saúde (BVS) e Scientific Electronic Library Online (Scielo), limiting the search period from 2013 to 2023 and using the descriptors in portuguese/english: transtornos da articulação temporomandibular/temporomandibular joint disorders, articulação temporomandibular/temporomandibular joint, artrocentese/arthrocentesis e artroscopia/ arthroscopy. Results: in total, thirty-three original scientific articles plus one book were selected to compose this review. Final considerations: it was found that both arthrocentesis and arthroscopy are procedures capable of providing satisfactory results in reducing unwanted signs and symptoms caused by temporomandibular disorders, therefore being highly effective and safe surgical treatments, as both techniques have a low rate of postoperative complications.